Implementasi Sertifikasi Produk Halal Pada Restoran di Kota Pekanbaru Berdasarkan Undang-Undang Nomor 33 Tahun 2014 - Eko Setiawan; Zainudin Hasan (Jurnal Terekam Jejak, 2024)
Law Number 33 of 2014 concerning Halal Product Guarantees stipulates that every product circulating in Indonesia must have halal certification. However, in practice, many products circulating in the community do not have a halal guarantee. This writing aims to analyze the implementation of Halal Product Certification in Restaurants in Pekanbaru City in accordance with Law Number 33 of 2014. The research method used is a sociological method. The research results show that there are still many business actors in Pkanbaru City, especially eateries and restaurants, that do not have halal certificates. This is caused by the mindset of business actors, low levels of compliance, and lack of supervision and control. Efforts that can be made by the Pekanbaru City government are to increase awareness of business actors to obtain halal certification, change their mindset, increase compliance, and increase supervision and control.